Performance level influences racing profiles of 1-km time trial in male high school cyclists - Nakamura, T.; Izumi, T.; Ozaki, H.; Naito, H.; Katamoto, S. (Journal of Science and Cycling, 2025)
Analyses of 1-km time trial (TT) racing profiles specifically for high school cyclists are lacking. This study aimed to clarify the racing profiles of male high school cyclists in a 1-km TT. The 1-km TT performance was analyzed in 50 male high school cyclists who participated in competitions held on the same track (333.3 m). The cyclists were divided into the High (n = 25, 72.9 ± 2.0 seconds) and Low (n = 25, 79.9 ± 3.1 seconds) groups based on their 1-km TT performance. We obtained panning shots of cyclists during the 1-km TT race and calculated the section velocity at every 83 m, average velocity, peak velocity, normalized velocity, and fatigue index from lap times. Analysis of variance showed significant main effects for section velocities and group, as well as a significant interaction in the 1-km TT velocity curve. The peak velocity was significantly higher in the High group than in the Low group (p = 0.000). However, the fatigue index did not differ between the groups. Significant negative correlations were found between 1-km TT record and velocity in each section and peak velocity in both groups (p < 0.05 or p < 0.01). In conclusion, the racing profiles of 1-km TT related to better performance are determined by higher peak velocity but are not influenced by the rate of velocity decline after reaching the peak velocity in male high school cyclists.